Recommendations for the management of comorbidity in hidradenitis suppurativa. (12th September 2017) - Dauden, E.; Lazaro, P.; Aguilar, M.D.; Blasco, A.J.; Suarez, C.; Marin, I.; Queiro, R.; Bassas‐Vila, J.; Martorell, A.; García‐Campayo, J.
Abstract: Background: The association between hidradenitis suppurativa (HS) and some diseases is becoming relevant in recent years. Providing appropriate management of HS from an early stage requires to include prompt diagnosis and treatment of concomitant diseases and to prevent any potential comorbidity. This approach should consider the adverse events of the drugs used to treat HS potentially related to the onset of a comorbidity. Objective: To provide the dermatologist with an accurate, easily used tool that will inform the diagnosis of HS comorbidity, and to facilitate decision‐making regarding the referral and treatment of patient with HS‐associated comorbidity. Methods: These recommendations have been developed by a working group composed of seven experts (three dermatologists, a cardiovascular specialist internist, a rheumatologist expert in spondyloarthritis, a gastroenterologist and a psychiatrist) and a team of three methodologist researchers. The expert group selected the HS comorbidities considered in these recommendations through a literature review. The recommendations on diagnostic criteria are based on the relevant clinical practice guidelines for each of the comorbidities and on the recommendations of the experts. The information regarding the repercussion of HS medical treatments on associated comorbid diseases was obtained from the summary of product characteristics of each drug. Results: The comorbidities considered in this guide are as follows: cardiovascular risk factors (diabetes, dyslipidaemia, obesity, hypertension and metabolic syndrome), inflammatory bowel disease, inflammatory joint disorders and psychological disorders (anxiety and depression). In addition, the association between HS and the consumption of alcohol and tobacco is included. The tables and figures are a precise, easy‐to‐use tool to systematize the diagnosis of comorbidity in patients with HS and facilitate the decision‐making process regarding referral and treatment of patients with an associated disease. Conclusion: The application of these recommendations will facilitate the dermatologist practice and benefit HS patients' health and quality of life.